Enhancing Employee Performance: The Role of Effective Communication and Work Motivation - Nazwa Hamidah; Siti Chanifah; Hendra Galuh Febrianto (Management Studies and Business Journal (PRODUCTIVITY), 2025)
In today's dynamic business environment, enhancing employee performance remains a critical challenge for organizations. This study examines how communication skills and work motivation influence employee performance at PT. Parison Asia Pacific, a company facing productivity challenges common in its industry. Using a quantitative approach with census sampling, the research gathered comprehensive data from all employees through questionnaires and observations. The analysis employed rigorous statistical methods to assess the relationships between variables. Findings demonstrate that both communication skills and work motivation significantly contribute to improved employee performance, with these factors collectively accounting for a substantial portion of performance variation. The study provides valuable insights for human resource management by highlighting the importance of effective communication and motivational strategies in workplace settings. Its practical contributions include specific recommendations for employee development programs and performance enhancement initiatives. The research adds to existing literature by offering empirical evidence from an Asian corporate context, while its comprehensive sampling approach strengthens the reliability of findings. These results not only benefit PT. Parison Asia Pacific in addressing its productivity challenges but also offer transferable knowledge for similar organizations seeking to optimize workforce performance through improved communication and motivation strategies.